Picture-based crop monitoring is adopted by six institutions to improve their agricultural insurance and financing services - CGIAR Platform for Big Data in Agriculture (2020)
Picture-Based Insurance provides affordable high-quality crop insurance by using smartphone images of smallholders’ crops for settlement of claims. The research led to adoption of picture-based crop monitoring by private companies HDFC ERGO General Insurance (India), Dvara E-Registry (India), and ACRE Africa (Kenya); government of India, and development organizaions including the R4 Rural Resilience Initiative (Ethiopia) and the Centre for Agriculture and Bioscience International (CABI) (India, Kenya), creating opportunities to strengthen crop insurance, financing and agro-advisories for millions of farmers.